Examining Teacher Job Satisfaction Levels During a Pandemic: The Role of Transformational Leadership, Work-Life Balance and Interpersonal Communication - Butarbutar, Marisi; Efendi, Efendi; Gheta, Antonius Philippus Kurniawan; Agustina, Titien; Sudirman, Acai (FKIP Universitas Lampung, 2022)
Objectives: The main objective of this study is to determine the contribution of transformational leadership, work-life balance, and interpersonal communication in encouraging teacher job satisfaction. Methods: The sample in this study amounted to 110 respondents. Data analysis using the SPSS application by displaying the results of data processing through research instrument testing with validity and reliability tests, multiple regression analysis, coefficient of determination and hypothesis testing. Findings: Based on the results of data analysis, it is concluded that transformational leadership and interpersonal communication contributes positively and significantly to job satisfaction. The results of subsequent studies confirmed that work-life balance contributed positively but not significantly to job satisfaction. Conclusions: The role of transformational leadership supported by interpersonal communication and good work life balance is needed by teachers to carry out activities, especially during the current pandemic. Keywords: transformational leadership, work-life balance, interpersonal communications, job satisfaction.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202202